2013
DOI: 10.1371/journal.pone.0056224
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Fucoidan against Renal Ischemia–Reperfusion Injury via Inhibition of the MAPK Signaling Pathway

Abstract: BackgroundIschemia reperfusion injury (IRI) is a leading cause of acute kidney injury (AKI) in both native and transplanted kidneys. The objective of the present study was to evaluate whether low-molecular-weight fucoidan (LMWF) could attenuate renal IRI in an animal model and in vitro cell models and study the mechanisms in which LMWF protected from IRI.Methodology/Principal FindingsMale mice were subjected to right renal ischemia for 30 min and reperfusion for 24 h, or to a sham operation with left kidney re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
50
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 51 publications
0
50
0
1
Order By: Relevance
“…19 In addition, it has obvious protective effects against brain inflammation and renal ischemia-reperfusion injury. 17,18 Here we demonstrated that LMWF corrected the impaired endothelium-dependent vasorelaxation and eNOS function in diabetic rats. Importantly, these effects of LMWF are through the protections of eNOS phosphorylation at Ser1177 residue and its expression in vasoendothelium, highlighting its effectiveness on dysfunctional endothelium, and thus anti-hypertension in diabetic animals.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…19 In addition, it has obvious protective effects against brain inflammation and renal ischemia-reperfusion injury. 17,18 Here we demonstrated that LMWF corrected the impaired endothelium-dependent vasorelaxation and eNOS function in diabetic rats. Importantly, these effects of LMWF are through the protections of eNOS phosphorylation at Ser1177 residue and its expression in vasoendothelium, highlighting its effectiveness on dysfunctional endothelium, and thus anti-hypertension in diabetic animals.…”
Section: Discussionmentioning
confidence: 67%
“…In previous studies, we have successfully prepared and characterized a low-molecular-weight fucoidan (LMWF, 7000 Da) from L aminaria japonica that shares similar biological activities with other fucoidans. [16][17][18] In particular, LMWF has an advantage over the others in that it exerts antithrombotic effect without impacting coagulation, 19 thus it has a lower hemorrhagic risk than other fucoidans. 14,15 Therefore, we hypothesized that LMWF may protect against the endothelial and vascular disorders caused by diabetes.…”
mentioning
confidence: 99%
“…However, all of their phosphorylation levels are altered under certain conditions. For instance, the phosphorylation of p38, ERK1/2 and JNK is significantly increased during hypoxia-reoxygenation in the human kidney cells [28]. Our recent studies found that ERK1/2 and p38 were dramatically activated in rat kidney epithelial cells (NRK-52E) under hypoxic conditions (Fig.…”
Section: Introductionmentioning
confidence: 80%
“…However, MAP kinases and PI3K/Akt/mTOR sig naling are thought to be implicated in the initiation and progression of IRinduced inflammatory responses (51)(52)(53)(54). We first examined the impact of aloperine on MAP kinase activities.…”
Section: Discussionmentioning
confidence: 99%